2010
DOI: 10.1097/ten.0b013e3181c9f2c0
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Depression in Turkish Patients With Diabetes and Diabetic Complications

Abstract: Objectives:In order to ascertain the impact of diabetes and diabetic complications on the risk of depression in the Turkish population, the Beck Depression Inventory (BDI) was used to investigate the frequency of depression in type 1 and type 2 diabetes mellitus patients (T1DM and T2DM) compared to controls (nondiabetic population). The influence of sociodemographic and other baseline characteristics on depression in DM patients and controls was also investigated. Patients and Methods: A total of 500 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Naughton and colleagues (17) found that QOL was better among patients with T1DM using insulin pump vs insulin injections. In a study involving patients with T1DM and type 2 diabetes mellitus (T2DM), frequency of depression was higher among patients with T2DM receiving insulin than in patients with T2DM without receiving insulin (18). The frequency of depression was highest among patients with T1DM in the same study (18).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Naughton and colleagues (17) found that QOL was better among patients with T1DM using insulin pump vs insulin injections. In a study involving patients with T1DM and type 2 diabetes mellitus (T2DM), frequency of depression was higher among patients with T2DM receiving insulin than in patients with T2DM without receiving insulin (18). The frequency of depression was highest among patients with T1DM in the same study (18).…”
Section: Discussionmentioning
confidence: 96%
“…Higher depression and anxiety scores were detected in patients with neuropathy and nephropathy. Saglam et al (18) have found that the rate of depression was higher when retinopathy and neuropathy were present. The present study has some limitations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the 268 literatures retrieved, a total of 20 independent studies as well as a total of 19 had been incorporated in line with the inclusion and exclusion criteria of literature by use of the blind method [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. These included 3 articles about type I diabetes, 12 about type II diabetes, 5 about types I and II; and 1 article studied the types I and II diabetes independently (Figure 1).…”
Section: Characteristics Of Literatures Includedmentioning
confidence: 99%